Calculation Method of Geometrical Center and Tooth Profile Error Calculation of Large Cylindrical Gear - Zhao Jun; Ye Ting; Guo Tiantai; Kong Ming; Wang Daodang; Lu Shouchuang (Jixie chuandong)
Calculation of gear geometrical center is an important issue in measurement of large gears. On the basis of the establishment of discrete data model of involute gear,a method to calculate the geometrical center of large cylindrical gear is put forward,and the corresponding mathematical model is established. According to the calculated result of gear center,the gear tooth profile error is calculated,and compared with the calculated result with the standard gear geometrical center known. The simulation results show that after adding random noise of the amplitude of 0 318 μm on the grade 8 large gear,the calculated maximum error of gear geometrical center is less than or equal to 1 μm,while the gear tooth profile error between the theoretical value and calculated result is less than or equal to 10 μm,which suggests that the method can be effectively applied to the measurement of large cylindrical gears.